Pengaruh Religiusitas, Lingkungan Keluarga dan Efikasi Diri terhadap Minat Berwirausaha Mahasiswa - Reza Triandini (Universitas Negeri Padang, 2022)
This study aims to determine the influence of religiosity, family environment and self-efficacy on entrepreneurial interests. The type of research is ex post facto. The research population is Universitas Negeri Padang students who received PMW in 2017/2018. Sampling technique using probability sampling technique , with sample is 80 students. Research instruments using questionnaires. Data analysis techniques using multiple linear regression. The results showed that simultaneously religiosity, family environment and self-efficacy influence the interest in entrepreneurship. In part, religiosity and the family environment influence the interest in entrepreneurship. Meanwhile, self-efficacy has no effect on entrepreneurial interests. The results of this study can be used as a guideline to increase students' interest in entrepreneurship.